(untitled) (Journal of humanities and social sciences exploratio, 2025)
William Somerset Maugham’s "The Veil" is often interpreted under the tradition of women’s coming-of-age novels, believing that the heroine Katie has achieved spiritual sublimation and growth in the suffering experience of Meitan Province. This article takes the linear narrative as the starting point and proposes that Katie’s awakening is a process of anti-growth. By tracing the germination and development of Katie’s self-consciousness, this article demonstrates that Katie’s awakening began with the shattering of external illusions but fell into the vacuum of inner value; Although she gained freedom of choice, she could not bear the weight of this freedom, tearing each other between desire and reason, exposing the fragility and vanity of her subjectivity. This article concludes that Katie’s journey does not lead to solid self-realization but ends with a clear awareness of existence and nothingness, and her growth is unfinished and paradoxical. This "anti-growth" narrative is Maugham’s pessimistic discovery of the inner dilemma encountered by modern people in their search for meaning.